SEASN THE BEST PLATFORM TO DISCUSS ASEAN SUSTAINABILITY ISSUES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 9 December 2015 – The establishment of South East Asia Sustainability Network (SEASN) indirectly would provide more space for ASEAN community members to collaborate in the exchange of ideas for advancing the state of the diverse cultures of the ASEAN countries.